Critical discourse analysis on copywriting in 2019 Malaysia aidilfitri television advertisements - Roslan, Nur Widad (2021)
Television advertisement is the main medium for brands of products or services to transmit messages to consumers. The copywriting in the advertisement should be intelligible in order for consumers to grasp the message. However, the contents of television advertisements nowadays do not use quality copy. Consumers feel that they have been cheated as the advertisements lead to misconception. In addition, the brands are not using consumers’ interest based on the contents of the advertisements. The contents are sometimes dubious and is not delivered properly among the consumers. With this, it is important to understand the discourse in the copywriting of the advertisements. Other than that, the content in Aidilfitri advertisements use a more emotional approach, hence it is more emotional and uses a more complex copy, as opposed to the product centric copy that only highlight the product benefits and features. Therefore, this study focuses on the implicit messages behind the complex emotional copy. This study applied the critical discourse analysis from Fairclough 1995, to reveal the implicit messages and hidden agenda from 2019 Malaysia Aidilfitri television advertisements. The objectives of this study are to identify and discuss the content and context of critical discourse in Malaysia Aidilfitri television advertisements’ copywriting. This is a qualitative study and the samples are eight 2019 Aidilfitri television advertisements which were recorded and analysed by using Fairclough’s 1995 three-dimension of critical discourse analysis. The threedimensions are textual analysis, discourse practice analysis and social practice analysis. The data obtained are analysed using Fairclough’s 1995 critical discourse analysis. In addition, two educational experts’ opinions will be sought to further strengthen the analysis of the textual, discourse and social practice analysis. As for objective 1, the results of the study revealed that the themes consist of family, tradition and value oriented. This showed that the themes compliment with the metaphor, repetition and conjunction used in the Aidilfitri television advertisements. Subsequently, the results for objective 2 showed that intertextuality of presupposition, metadiscourse and deny were used to influence the viewers perception while interdiscussion of narrative, argumentative expository and expressive were used to outline and make the storyline of the television advertisement more interesting. Consequently, the results for objective 3 revealed that the social practice analysis of economy, education and politics had influenced the type of copy used in the television advertisements. It can be seen that the study on critical discourse analysis on Malaysia Aidilfitri television advertisement will help consumers in better understanding and content with the copy. Also, the study implicates copywriters, product owner and advertisement agency in focusing on the quality of the copy in order to satisfy the needs of the consumers. It is hoped that this study will help them to plan and produce comprehensible and interesting copies for Malaysia festive advertisement copies.